2016
DOI: 10.1021/acs.jpcc.6b02910
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite-Catalyzed Disproportionation of iso-Propylbenzene: Identification of Reaction Intermediates and Mechanism

Abstract: The catalytic properties of a series of large-pore (H-Y, H-beta, H-mordenite, and H-UZM-35) and medium-pore zeolites are compared in isopropylbenzene (iPB) disproportionation. Among the zeolite catalysts studied here, H-UZM-35 with a three-dimensional framework consisting of one type of straight 12-ring channels and two types of tortuous 10-ring channels was found to show a comparable di-isopropylbenzenes (DiPBs) yield to that of H-beta with two intersecting 12-ring channels, the best catalyst tested for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…TNU-9 has been investigated as ac atalystf or both acid and redox reactions:T oluene [9b] and ethylbenzene [10] disproportionation, the methanol-to-hydrocarbons reaction (MTH), [11] the alkylationo fb enzene and toluene with methanol, ethanol, and isopropanol, [12] the isomerization and disproportionation of mxyleme, [9b, 13] the alkylation of benzene with n-hexane, [14] the hydroisomerization of n-hexane, [15] the alkylation of phenol with propylene, [16] and the disproportionation of n-propylbenzene [17] and isopropylbenzene [18] are examples of acid-catalyzed reactions that have been performed with the H-form of the TNU-9 zeolite.R edox-catalyzed reactions use transition-metal-exchanged TNU-9, for example, Co-TNU-9 and Cu-TNU-9, fort he selectivec atalytic reduction of NO, [19] and Cu-TNU-9 for the oxidation of propane. [20] Studies have shown that the TNU-9 zeolite represents ah ighly promising zeolite matrix for both acidand redox-catalyzed reactions.H owever,t he potential of this new zeolite cannot be fully evaluated without the knowledge of the aluminumo rganization in the TUN framework, which is not currently known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNU-9 has been investigated as ac atalystf or both acid and redox reactions:T oluene [9b] and ethylbenzene [10] disproportionation, the methanol-to-hydrocarbons reaction (MTH), [11] the alkylationo fb enzene and toluene with methanol, ethanol, and isopropanol, [12] the isomerization and disproportionation of mxyleme, [9b, 13] the alkylation of benzene with n-hexane, [14] the hydroisomerization of n-hexane, [15] the alkylation of phenol with propylene, [16] and the disproportionation of n-propylbenzene [17] and isopropylbenzene [18] are examples of acid-catalyzed reactions that have been performed with the H-form of the TNU-9 zeolite.R edox-catalyzed reactions use transition-metal-exchanged TNU-9, for example, Co-TNU-9 and Cu-TNU-9, fort he selectivec atalytic reduction of NO, [19] and Cu-TNU-9 for the oxidation of propane. [20] Studies have shown that the TNU-9 zeolite represents ah ighly promising zeolite matrix for both acidand redox-catalyzed reactions.H owever,t he potential of this new zeolite cannot be fully evaluated without the knowledge of the aluminumo rganization in the TUN framework, which is not currently known.…”
Section: Introductionmentioning
confidence: 99%
“…TNU‐9 has been investigated as a catalyst for both acid and redox reactions: Toluene and ethylbenzene disproportionation, the methanol‐to‐hydrocarbons reaction (MTH), the alkylation of benzene and toluene with methanol, ethanol, and isopropanol, the isomerization and disproportionation of m ‐xyleme, the alkylation of benzene with n ‐hexane, the hydroisomerization of n ‐hexane, the alkylation of phenol with propylene, and the disproportionation of n ‐propylbenzene and isopropylbenzene are examples of acid‐catalyzed reactions that have been performed with the H‐form of the TNU‐9 zeolite. Redox‐catalyzed reactions use transition‐metal‐exchanged TNU‐9, for example, Co‐TNU‐9 and Cu‐TNU‐9, for the selective catalytic reduction of NO, and Cu‐TNU‐9 for the oxidation of propane .…”
Section: Introductionmentioning
confidence: 99%
“…H–Y (framework type FAU; Si/Al = 15) and NH 4 -beta (BEA*; Si/Al = 13) were obtained from PQ, while H-mordenite (MOR; Si/Al = 10) and NH 4 -ZSM-5 (MFI; Si/Al = 14) were purchased from Tosoh. To ensure that these zeolites were completely in their proton form, they were refluxed twice in 1.0 M NH 4 (NO 3 ) 3 solutions (2.0 g of solid per 100 mL of solution) for 6 h followed by calcination at 823 K for 4 h. UZM-35 (MSE; Si/Al = 9), NU-87 (NES; Si/Al = 25), and TNU-9 (TUN; Si/Al = 18) were synthesized, converted into their proton form, and characterized by powder X-ray diffraction, scanning electron microscopy, elemental and thermal analyses, N 2 adsorption, and IR measurements of adsorbed pyridine, as described elsewhere. GC-MS analyses of the organic compounds formed within zeolite catalysts after transalkylation of i PB with toluene were carried out following the procedures given in our previous papers. , The GC-MS total ion chromatograms were recorded on an Agilent 7890A gas chromatograph equipped with an Agilent 5975C mass selective detector, and the organic compounds extracted were identified by comparing with the NIST database . The characterization data for all zeolite catalysts studied here are summarized in Table .…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The zeolite-catalyzed reactions of aromatic hydrocarbons we have studied include the isomerization and disproportionation of m -xylene; disproportionation of ethylbenzene, n -propylbenzene, iso -propylbenzene, and 1,2,4-trimethylbenzene; and transalkylation of 1,2,4-trimethylbenzene with toluene. Ex situ gas chromatography–mass spectrometry (GC-MS) was the main tool we used in the characterization of bimolecular aromatic compounds formed during each reaction within the void spaces of zeolite catalysts. Contrary to our expectation, this simple analytical method has always allowed us to find unprecedented type(s) of bimolecular reaction intermediates and thus to propose new reaction pathways for the aromatic hydrocarbon conversions described above.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, only a few reports on the acidic catalysis and the acid site location of UZM-35 compared to that for MCM-68 so far. [23][24][25][26] Considering our finding that the use of different OSDAs leads to the different framework Al distribution, we have expected that there are significant differences in the framework Al distribution and acidic and catalytic properties between UZM-35 and MCM-68.…”
Section: Introductionmentioning
confidence: 99%